Blood histamine levels (BHL) in infants and children with respiratory and non-respiratory diseases - C. Ponvert; L. Galoppin; J. Paupe; J. de Blic; M. Le Bourgeois; P. Scheinmann (Mediators of Inflammation)
Background: Blood histamine levels are decreased after severe allergic reactions and in various chronic diseases.